2022
DOI: 10.3389/fpls.2022.851531
|View full text |Cite
|
Sign up to set email alerts
|

ZmPP2C26 Alternative Splicing Variants Negatively Regulate Drought Tolerance in Maize

Abstract: Serine/threonine protein phosphatase 2C (PP2C) dephosphorylates proteins and plays crucial roles in plant growth, development, and stress response. In this study, we characterized a clade B member of maize PP2C family, i.e., ZmPP2C26, that negatively regulated drought tolerance by dephosphorylating ZmMAPK3 and ZmMAPK7 in maize. The ZmPP2C26 gene generated ZmPP2C26L and ZmPP2C26S isoforms through untypical alternative splicing. ZmPP2C26S lost 71 amino acids including an MAPK interaction motif and showed higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…ZmPP2C26 negatively regulates drought tolerance by dephosphorylating mitogenactivated protein kinases (ZmMAPK3 and ZmMAPK7). Yeast two-hybrid screening showed that ZmPP2C26 interacts with ZmMAPK but not ZmPYLs, confirming the role of ZmPP2C26 in MAPK signaling (Lu et al, 2020(Lu et al, , 2022. However, the roles of ZmMAPK3 and ZmMAPK7 in the response of maize to drought stress require further study.…”
Section: Genes That Function In Drought Resistance During the Seedlin...mentioning
confidence: 80%
See 1 more Smart Citation
“…ZmPP2C26 negatively regulates drought tolerance by dephosphorylating mitogenactivated protein kinases (ZmMAPK3 and ZmMAPK7). Yeast two-hybrid screening showed that ZmPP2C26 interacts with ZmMAPK but not ZmPYLs, confirming the role of ZmPP2C26 in MAPK signaling (Lu et al, 2020(Lu et al, , 2022. However, the roles of ZmMAPK3 and ZmMAPK7 in the response of maize to drought stress require further study.…”
Section: Genes That Function In Drought Resistance During the Seedlin...mentioning
confidence: 80%
“…Studies in the model plant Arabidopsis have revealed that when plants sense osmotic stress caused by drought, the levels of the phytohormone ABA dramatically increase, inducing the transcriptional regulation of genes to reduce water loss by promoting stomatal closure (Yoshida et al, 2014;Agurla et al, 2018;Cao et al, 2021). Over the last 10 years, many studies in crop plants have confirmed the important roles of ABA signaling components in drought resistance (Xiang et al, 2017;He et al, 2019;Lu et al, 2020Lu et al, , 2022. Several novel factors involved in regulating drought resistance in crops via an ABA-dependent pathway have also been identified (Xiang et al, 2017).…”
Section: Genes That Function In Drought Resistance During the Seedlin...mentioning
confidence: 99%
“…Drought stress is a major environmental factor affecting crops' growth and productivity, leading to significant socioeconomic damage (Sinha et al, 2011;Raza et al, 2022a). Drought occurs when water uptake within the plant by root is reduced due to low moisture in the soil, afflicting root morphology growth and physiology owing to wilt conditions, and consequently reducing the annual yield in plants (Aditi et al, 2020;Ahmad et al, 2021;Feng et al, 2022;Lu et al, 2022;Raza et al, 2022a). Biochemical and transcriptional studies have elaborated the MAPK response in drought in grassy and woody plants (Huang et al, 2020).…”
Section: The Role Of Mapks Under Drought and Oxidative Stressmentioning
confidence: 99%
“…The response of maize shoots under drought stress involved proteins related to photosynthesis, amino acids, sugar/starch metabolism, and redox regulation [ 101 ]. The phosphoproteomic analysis in maize revealed that serine/threonine protein phosphatase 2C (ZmPP2C26) altered the phosphorylation level of proteins involved in photosynthesis [ 102 ]. Furthermore, leaf proteins involved in redox homeostasis and the electron transport chain helped in drought tolerance [ 103 ].…”
Section: Crop Proteomics In Understanding Environmental Stress Responsesmentioning
confidence: 99%